Spatiotemporal Evolution and Simulation Prediction of Ecosystem Service Function in the Western Sichuan Plateau Based on Land Use Changes - Xiang, Mingshun; Yang, Jin; Li, Wenheng; Song, Yueting; Wang, Chunjian; Liu, Yan; Liu, Mengli; Tan, Yuxiang (Frontiers in Environmental Science, 2022)
Being closely related to ecosystem services, land use changes can affect ecosystem service functions by acting on ecosystem patterns and its processes, thus having impact on regional sustainable development. Taking the Western Sichuan Plateau as the study area based on land use data from 1990 to 2020, the CA-Markov model was employed to predict the land use pattern under natural change scenarios, and the improved InVEST model and equivalent method were used to evaluate the ecosystem services in the study area from two different perspectives, as to analyze the evolution trend. The results show that: (1) From 1990 to 2020, the carbon storage in the Western Sichuan Plateau showed a fluctuating increase, with an average annual increase of 3.17×107 t, of which the total contribution rate of woodland and grassland to the total carbon storage exceeded 95%. In recent 30 years, the carbon storage of the Western Sichuan Plateau has little spatial variation, with the increase and decrease regions accounting for less than 5% with overall sporadically dots-like distribution. (2) Ecosystem Service Value (ESV) increased by 1.36 ×1010 yuan in the past 30 years, which was similar to carbon storage and showed a wave-like increase; the contribution rate of woodland to the total ESV of the study area was more than 68%, occupying the dominant position. ESV was generally stable in the past 30 years, and the area with significant changes accounted for less than 9%, mainly located in the northeast and southwest of the study area. (3) In the next 10 years, under the current ecological protection measures, the carbon storage and ESV of the Western Sichuan Plateau will increase by 5.3980×107 t and 2.4087×109 yuan compared with that of 2020, indicating a positive development of ecosystem service function. This study results provides a scientific basis for the adjustment of land use structure and the management decision of ecological environment protection in the Western Sichuan Plateau.